EU enlargement and immigration - Margit Kraus; Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
This paper assesses the consequences of EU enlargement for East West migration. In the theoretical part, we identify several factors in addition to the reduction of moving costs by which EU membership influences migration. Specifically, EU accession affects income gaps. Moreover, if EU membership is refused, fear of future restrictions on immigration will lead to increased current migration. Additionally, casual evidence from the 1980s EU South enlargement is examined. Since then no increases in migration flows from Spain, Portugal and Greece were observed. We conclude that granting EU accession to Eastern European countries will not necessarily induce massive East-West migration flows.
Keywords: F22; J61; 330; Europe; Migration; Uncertainty; Enlargement; Internationale Wanderung; Einkommen; EU-Erweiterung; Schätzung; Osteuropa; EU-Staaten; Südeuropa